Using variational formulae for solving extremal problems in linearly‐invariant classes - Kirjackij, E. G. (Mathematical Modelling and Analysis, 1997)
“Using variational formulae for solving extremal problems in linearly‐invariant classes”Mathematical Modelling Analysis, 2(1), p. 105-116.First Published Online: 14 Oct 2010